Toys for children with the concept of STEM: study of the result from children’s playing activities - Songwut Egwutvongsa (Journal for the Education of Gifted Young Scientists, 2021)
This research aimed to examine the result from toy invention with the concept of STEM. The testers comprised 36 people who were the parents and children aged between five to seven years old that used the service of a child development center in Buriram Municipality in Thailand. Additionally, they were selected by purposive sampling that used multiple regression analysis to show the result from the testing of the newly designed toys as the concept of STEM. The results found that the toys had a satisfaction level of the Good (mean=4.333; S.D.=0.652) with the regression equation 𝑌̂ = 0.234 + [0.741 X1] + [0.106 X2] + [0.049 X3] + [0.071 X4] to explain the changing of the level of satisfaction to be 72.73% (r²=0.7273). Research of the playing design as the concept of STEM at this time, Able to meet learning goals based on STEM concepts to an excellent level.
Keywords: Educational Games and Gamification; Neuroscience, Education and Cognitive Function; Science Education and Pedagogy